Rendezvous with the Senses, a Brainstem's Journey - Tenecela, Edison (Ars Medica, 2025)
"Rendezvous with the Senses, a Brainstem's Journey" is an art piece that tries to capture our senses embedded in nature itself. As we take a dive into the image, we can gradually discover subtleties such as a nose, a thumbprint, an eye, lips, and ears throughout the scenery. These components are not solitary elements but are rather interconnected. Similarly, we may also appreciate elements of our brain reflected by the insect’s body (brainstem and thalamus) and antennae (olfactory bulb) as a representation of our body's central processor, our nervous system. The title is called "Rendezvous with the Senses, a Brainstem's Journey" because it aims at appreciating our evolution from strict survival to deeply analyzing our surroundings. From using our most primitive brain, the brainstem, for vital functions such as breathing, to using our senses to process and develop meaning from an abstract concept or image.